Digital Maturity and Transformation Readiness Across Indonesian Industries - Yane Devi Anna; Yulina Ismiyanti; Richard Evans (APTISI Transactions on Management (ATM), 2026)
Indonesia is experiencing a rapid digital transformation driven by national initiatives such as Making Indonesia 4.0 and the Digital Economy Roadmap 2030. However, prior studies consistently report uneven digital maturity across industries due to disparities in infrastructure, digital skills, leadership commitment, and strategic alignment. This study adopts a Systematic Literature Review (SLR) to synthesize empirical and conceptual evidence on digital maturity and digital transformation readiness across industries in Indonesia and comparable emerging economies. The review focuses on six dominant dimensions identified across prior studies, namely digital strategy alignment, IT infrastructure, data analytics capability, leadership commitment, employee capability, and innovation culture. The synthesis reveals that banking and financial services exhibit the highest level of digital maturity, followed by manufacturing and logistics. At the same time, MSMEs, education, and healthcare remain in early to developing stages. Leadership commitment, workforce digital skills, and data analytics capability consistently emerge as the most critical drivers of transformation readiness. This study contributes theoretically by integrating fragmented findings on digital maturity into a coherent conceptual framework relevant to emerging economies. Practically, the results support national digital policy development and align with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure) by emphasizing inclusive digital capability development.